PENERAPAN PENDEKATAN CONTEXSTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 019 TELUK PIYAI KECAMATAN KUBU - ', Mardiana Mardiana; ', Lazim N Lazim N; ', Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This study departed from low yields social studies students, with anaverage value of 64.05 class. While the value of minimum completeness criteria(KKM) IPS is 65 Aiming to improve learning outcomes IPS 019 fourth gradestudents of SDN Gulf Piyai Kubu district of Rokan Hilir. Formulation of theproblem: Is the application of CTL learning model to improve learning outcomesIPS 019 fourth grade students of SDN Gulf Piyai Kubu district of Rokan Hilir.Improved learning outcomes before PTK with an average of 64.05 with thecategory of less than one cycle after an increase by an average of 70.75 withenough categories and the second cycle with an average of 82.25 with very goodcategory. Overall, therefore, an increase in student learning outcomes from abase score of 6.7 and kesiklus one of two kesiklus base score of 18.2. While theactivities of students in the first cycle with an average of 68.75% in the secondcycle with an average of 83.33%. While the activity of the teacher on the firstcycle with an average 72.91% in the second cycle reaches 87.49%. These resultsprove that the application of CTL Learning Model can improve learning outcomesIPS 019 fourth grade students of SDN Gulf Piyai Kubu district Rokan Hilir.Keywords: Contextual Teaching and Learning, IPS leaning outcome